The Influence of Macroeconomic Factors on Economic Growth on Indonesia's Receipt and Distribution of ZIS Funding - Sari, Anggi Puspita; Sukardi, Budi (ASFA Foundation, 2024)
Indonesia has significant potential for distributing zakat, which can effectively address issues such as poverty and inequality in the nation. The ratio of ZIS funds received and disbursed by BAZNAS RI serves as the dependent variable in this analysis, which utilizes secondary data from January 2017 to December 2021, illustrating the quantitative approach employed in this investigation. Macroeconomic variables that affect economic growth, such as GDP, interest rates, inflation, poverty, and total money in circulation (JUB), are the independent variables. This study utilized multiple linear regression analysis with the Least Squares (LS) methodology. The classical assumption test consists of many linear regression tests such as Multicollinearity, Autocorrelation, Heteroscedasticity, Normality, and Linearity. The amount of Money in Circulation (JUB) that decreases the poverty rate, and the effect of decreasing the unemployment rate in Indonesia are the findings of the study that will affect the feasibility of channeling ZIS funds in Indonesia. Therefore, it can be concluded that changes in the quantity of GDP, interest rates, and inflation will not affect the receipt or distribution of ZIS funds in Indonesia.